Optimization of filters and processing conditions for aerosol detection of relevant avian respiratory viruses in poultry under experimental and field conditions - Claudia Trenado; Pablo Cea-Callejo; Esperanza Gomez-Lucia; Samuel Novoa; Ricardo Madrid; Ana Doménech; Laura Benítez (Veterinary Microbiology, 2026)

Invasive Carpobrotus taxa reshape rhizosphere microbiome across native and non-native ranges - Marta Pérez-Diz; Jose A. Morillo; Berea Rodríguez-Addesso; Luís González; Jonatan Rodríguez; Paula Gervazoni; Giuseppe Brundu; Nicholas Saglimbeni; Carla M. D'Antonio; Johannes J. Le Roux; Lúa Lopez; Petr Pyšek; et al. (Perspectives in Plant Ecology, Evolution and Systematics, 2026)

Australian Acacia species impact soil bacterial communities abroad but not at home - Jonatan Rodríguez; Ana Novoa; Richard P. Duncan; Philip E. Hulme; Jan-Hendrik Keet; Ángel Valverde; Elizabeth M. Wandrag; Johannes J. Le Roux (Plant and Soil, 2026)

Carpobrotus taxa benefit more from clonal integration in their non-native than native ranges - Marta Pérez-Diz; Hana Skálová; Susan Canavan; María Loreto Castillo; Paula Gervazoni; Luís González; Petr Pyšek; Jonatan Rodríguez; Kateřina Štajerová; Giuseppe Brundu; Carla M. D’Antonio; Tom Dudley; et al. (Biological Invasions, 2026)
Understanding physiological integration in invasive clonal plants is relevant to invasion biology because resource transfer across ramets may allow alien plants to buffer spatial heterogeneity in their introduced areas. However, experimental evidence across native and non-native ranges is limited. Here, we tested whether physiological integration provides greater performance benefits to Carpobrotus taxa in non-native than native ranges. We grew clonal fragments under controlled conditions from eleven populations representing different genetic clusters across their native and non-native ranges. Connected recipient ramets showed higher growth than severed ones, with increased ramet length, node number, Branching and Vigor Indices, while connected donor ramets showed reduced growth, indicating resource redistribution within the clone. Plants from non-native ranges exhibited overall higher growth-related traits and chlorophyll content, suggesting enhanced growth and stress tolerance across genetic backgrounds. These results indicate that physiological integration allows Carpobrotus taxa to overcome environmental heterogeneity by reallocating resources among ramets, promoting clonal growth and expansion, and potentially increasing competitive ability in non-native ranges. Our findings provide experimental evidence across multiple populations that physiological integration can promote the ecological success of clonal invaders.

Marine heatwave associated Betanodavirus outbreak in wild groupers of the Azores - Inês Gomes; Ana Novoa-Pabon; Miriam Abbadi; Tobia Pretto; Joana Rosa; Luís Silva; Paulo Torres; Andrea Marsella; Pedro Afonso; Anna Toffan (Frontiers in Marine Science, 2025)
This study reports the first viral nervous necrosis (VNN) outbreak in wild dusky grouper ( Epinephelus marginatus ) in the North Atlantic, and the first detection of the virus in island grouper ( Mycteroperca fusca ). Most affected fish displayed typical VNN clinical signs and lesions, and laboratory analyses confirmed the virus as the primary cause of mortality. The majority of the diseased individuals were large adults, underscoring the risk to stock sustainability and conservation of this vulnerable and iconic species. Viral sequences were highly homogeneous (>99% nucleotide similarity), suggesting a single, recent introduction. The outbreak coincided with a severe marine heatwave affecting the Azorean Archipelago in the summer of 2024, during which sea surface temperatures exceeded 25 °C, the optimal range for the RGNNV genotype replication. The absence of fatalities in the eastern islands may be due to several factors, including heterogeneous introduction pathways, oceanographic differences, and lower grouper densities. This event highlights the vulnerability of long-lived, site-attached species to emerging pathogens, particularly under climate-driven stress. Effective management requires coordinated regional responses, ecosystem monitoring and early detection systems to prevent further spread and safeguard wild grouper populations.

Limited and socially unequal contributions of rain gardens to native biodiversity in a tropical megacity - Jonathan Almeida; Ana Novoa; Jean Paul Metzger (Urban Forestry & Urban Greening, 2025)

A spatiotemporal analysis of bovine brucellosis cases in dairy herds from Argentina, from 2014 to 2023 - María Belén Novoa; Nerina Patricia Aguirre; Estefanía Ugarte; Camila Nayla Foster; Ana Inés Molineri; Marcelo Lisandro Signorini; Alberto Martín Molina; Victor René Vanzini (Tropical Animal Health and Production, 2025)

Announcing the invasions newsletter - Ana Novoa; Susan Canavan; Katelyn T. Faulkner; Piero Genovesi; Deah Lieurance; Dan Simberloff; Hsiao-Hsuan Wang; Tsungai Zengeya; Laura A. Meyerson (Biological Invasions, 2025)

Effects of conspecific and congeneric soils and litters on the nodulation and growth of non-native invasive and native Prosopis species in arid deserts - Ali El-Keblawy; Elsiddig A.E. Elsheikh; Ana Novoa; Ross T. Shackleton; Mohamed Sheteiwy; Salma K. Shaltout (Journal of Arid Environments, 2025)

Culturomics and iEcology provide novel opportunities to study human and social dimensions of alien species introductions - Ana Novoa; Ivan Jarić; Pavel Pipek; Petr Pyšek (Trends in Ecology & Evolution, 2025)

Using the IUCN Environmental Impact Classification for Alien Taxa to inform decision‐making - Sabrina Kumschick; Sandro Bertolino; Tim M. Blackburn; Giuseppe Brundu; Katie E. Costello; Maarten de Groot; Thomas Evans; Belinda Gallardo; Piero Genovesi; Tanushri Govender; Jonathan M. Jeschke; Katharina Lapin; et al. (Conservation Biology, 2024)
The Environmental Impact Classification for Alien Taxa (EICAT) is an important tool for biological invasion policy and management and has been adopted as an International Union for Conservation of Nature (IUCN) standard to measure the severity of environmental impacts caused by organisms living outside their native ranges. EICAT has already been incorporated into some national and local decision‐making procedures, making it a particularly relevant resource for addressing the impact of non‐native species. Recently, some of the underlying conceptual principles of EICAT, particularly those related to the use of the precautionary approach, have been challenged. Although still relatively new, guidelines for the application and interpretation of EICAT will be periodically revisited by the IUCN community, based on scientific evidence, to improve the process. Some of the criticisms recently raised are based on subjectively selected assumptions that cannot be generalized and may harm global efforts to manage biological invasions. EICAT adopts a precautionary principle by considering a species’ impact history elsewhere because some taxa have traits that can make them inherently more harmful. Furthermore, non‐native species are often important drivers of biodiversity loss even in the presence of other pressures. Ignoring the precautionary principle when tackling the impacts of non‐native species has led to devastating consequences for human well‐being, biodiversity, and ecosystems, as well as poor management outcomes, and thus to significant economic costs. EICAT is a relevant tool because it supports prioritization and management of non‐native species and meeting and monitoring progress toward the Kunming–Montreal Global Biodiversity Framework (GBF) Target 6.

Economic costs of invasive non-native species in urban areas: An underexplored financial drain - Gustavo Heringer; Romina D. Fernandez; Alok Bang; Marion Cordonnier; Ana Novoa; Bernd Lenzner; César Capinha; David Renault; David Roiz; Desika Moodley; Elena Tricarico; Kathrin Holenstein; et al. (Science of The Total Environment, 2024)

Understanding the drivers of volcano deformation through geodetic model verification and validation - Josh Crozier; Leif Karlstrom; Emily Montgomery-Brown; Mario Angarita; Valérie Cayol; Mary Grace Bato; Taiyi A. Wang; Ronni Grapenthin; Tara Shreve; Kyle Anderson; Ana Astort; Olivier Bodart; et al. (Bulletin of Volcanology, 2023)

Performance of length-based assessment in predicting small-scale multispecies fishery sustainability - Wendell Medeiros-Leal; Régis Santos; Ualerson I. Peixoto; Morgan Casal-Ribeiro; Ana Novoa-Pabon; Michael F. Sigler; Mário Pinho (Reviews in Fish Biology and Fisheries, 2023)
Small-scale fisheries play a critical role in food security and contribute to nearly half of reported global fish catches. However, the status of most small-scale fisheries stocks is still poor. In data-limited situations, length-based methods have been widely applied to estimate reference points and to understand stock status. This study applied three different length-based assessment methods (length-based indicators—LBI, length-based spawning potential ratio—LBSPR, and the length-based Bayesian biomass approach—LBB) to predict fisheries stock sustainability in the Azores. Overall, the three methods showed robustness for 15 out of 18 stocks assessed and agreed on their exploitation status. The results showed that 45% of the Azorean stocks were classified as sustainable stocks , 33% possible rebuilding/overfished and 22% overfishing/overfished stock status. Sensitivity analysis showed that biases on the source of initial life-history parameters, especially the asymptotic length (L∞) and the ratio of natural mortality and growth coefficient (M/k), have a stronger influence on the reference points of conservation of mature individuals (LBI), spawning potential ratio and fishing mortality (LBSPR) and the biomass relative to the maximum sustainable yield (LBB). Furthermore, sensitivity analysis indicated that, among the three methods, LBI is more robust. Our findings provide some management recommendations such as (1) catches and effort should be reduced; (2) minimum landing size should be increased; (3) minimum hook size should be increased, to be applied mainly for those stocks classified as possible rebuilding/overfished and overfishing/overfished stock status. Graphical abstract

Carbon and nitrogen stable isotope compositions provide new insights into the phenotypic plasticity of the invasive species Carpobrotus sp. pl. in different coastal habitats - Marta Pérez-Diz; Berea Rodríguez-Addesso; Muhammad Iftikhar Hussain; Jonatan Rodríguez; Ana Novoa; Luís González (Science of The Total Environment, 2023)

Variation in defensive traits against herbivores of native and invasive populations of Carpobrotus edulis - Jonatan Rodríguez; Ana Novoa; Gastón Sotes; Aníbal Pauchard; Luís González (Biological Invasions, 2023)

Robust identification of potential habitats of a rare demersal species (blackspot seabream) in the Northeast Atlantic - Lola De Cubber; Verena M. Trenkel; Guzman Diez; Juan Gil-Herrera; Ana Maria Novoa Pabon; David Eme; Pascal Lorance (Ecological Modelling, 2023)

Energy consumption and indoor environmental quality evaluation of a cooperative housing nZEB in Mediterranean climate - Joana Ortiz; Juli Carrere; Jaume Salom; Ana M. Novoa (Building and Environment, 2023)

Exploring the performance of Biological Invasions in social media five years after opening its Facebook and Twitter accounts - Ana Novoa; Susan Canavan; Deah Lieurance; Daniel Simberloff; Laura A. Meyerson (Biological Invasions, 2023)

Consensus and controversy in the discipline of invasion science - Ross T. Shackleton; Giovanni Vimercati; Anna F. Probert; Sven Bacher; Christian A. Kull; Ana Novoa (Conservation Biology, 2022)
Approaches, values, and perceptions in invasion science are highly dynamic, and like in other disciplines, views among different people can diverge. This has led to debate in the field specifically surrounding the core themes of values, management, impacts, and terminology. Considering these debates, we surveyed 698 scientists and practitioners globally to assess levels of polarization (opposing views) on core and contentious topics. The survey was distributed online (via Google Forms) and promoted through listservs and social media. Although there were generally high levels of consensus among respondents, there was some polarization (scores of ≥0.39 [top quartile]). Relating to values, there was high polarization regarding claims of invasive species denialism, whether invasive species contribute to biodiversity, and how biodiversity reporting should be conducted. With regard to management, there were polarized views on banning the commercial use of beneficial invasive species, the extent to which stakeholders’ perceptions should influence management, whether invasive species use alone is an appropriate control strategy, and whether eradication of invasive plants is possible. For impacts, there was high polarization concerning whether invasive species drive or are a side effect of degradation and whether invasive species benefits are understated. For terminology, polarized views related to defining invasive species based only on spread, whether species can be labeled as invasive in their native ranges, and whether language used is too xenophobic. Factor and regression analysis revealed that views were particularly divergent between people working on different invasive taxa (plants and mammals) and in different disciplines (between biologists and social scientists), between academics and practitioners, and between world regions (between Africa and the Global North). Unlike in other studies, age and gender had a limited influence on response patterns. Better integration globally and between disciplines, taxa, and sectors (e.g., academic vs. practitioners) could help build broader understanding and consensus.

Introduction pathways of economically costly invasive alien species - Anna J. Turbelin; Christophe Diagne; Emma J. Hudgins; Desika Moodley; Melina Kourantidou; Ana Novoa; Philip J. Haubrock; Camille Bernery; Rodolphe E. Gozlan; Robert A. Francis; Franck Courchamp (Biological Invasions, 2022)
Introduction pathways play a pivotal role in the success of Invasive Alien Species (IAS)—the subset of alien species that have a negative environmental and/or socio-economic impact. Pathways refer to the fundamental processes that leads to the introduction of a species from one geographical location to another—marking the beginning of all alien species invasions. Increased knowledge of pathways is essential to help reduce the number of introductions and impacts of IAS and ultimately improve their management . Here we use the InvaCost database, a comprehensive repository on the global monetary impacts of IAS, combined with pathway data classified using the Convention on Biological Diversity (CBD) hierarchical classification and compiled from CABI Invasive Species Compendium, the Global Invasive Species Database (GISD) and the published literature to address five key points. Data were available for 478 individual IAS. For these, we found that both the total and annual average cost per species introduced through the ‘Stowaway’ (US$144.9bn; US$89.4m) and ‘Contaminant’ pathways (US$99.3bn; US$158.0m) were higher than species introduced primarily through the ‘Escape’ (US$87.4bn; US$25.4m) and ‘Release’ pathways (US$64.2bn; US$16.4m). Second, the recorded costs (both total and average) of species introduced unintentionally was higher than that from species introduced intentionally. Third, insects and mammals, respectively, accounted for the greatest proportion of the total cost of species introduced unintentionally and intentionally respectively, at least of the available records; ‘Stowaway’ had the highest recorded costs in Asia, Central America, North America and Diverse/Unspecified regions. Fourthly, the total cost of a species in a given location is not related to the year of first record of introduction, but time gaps might blur the true pattern. Finally, the total and average cost of IAS were not related to their number of introduction pathways. Although our findings are directly limited by the available data, they provide important material which can contribute to pathway priority measures, notably by complementing studies on pathways associated with ecologically harmful IAS. They also highlight the crucial need to fill the remaining data gaps—something that will be critical in prioritising limited management budgets to combat the current acceleration of species invasions.

Surprisingly high economic costs of biological invasions in protected areas - Desika Moodley; Elena Angulo; Ross N. Cuthbert; Brian Leung; Anna Turbelin; Ana Novoa; Melina Kourantidou; Gustavo Heringer; Phillip J. Haubrock; David Renault; Marine Robuchon; Jean Fantle-Lepczyk; et al. (Biological Invasions, 2022)
Biological invasions are one of the main threats to biodiversity within protected areas (PAs) worldwide. Meanwhile, the resilience of PAs to invasions remains largely unknown. Consequently, providing a better understanding of how they are impacted by invasions is critical for informing policy responses and optimally allocating resources to prevention and control strategies. Here we use the InvaCost database to address this gap from three perspectives: (i) characterizing the total reported costs of invasive alien species (IAS) in PAs; (ii) comparing mean observed costs of IAS in PAs and non-PAs; and (iii) evaluating factors affecting mean observed costs of IAS in PAs. Our results first show that, overall, the reported economic costs of IAS in PAs amounted to US$ 22.24 billion between 1975 and 2020, of which US$ 930.61 million were observed costs (already incurred) and US$ 21.31 billion were potential costs (extrapolated or predicted). Expectedly, most of the observed costs were reported for management (73%) but damages were still much higher than expected for PAs (24%); in addition, the vast majority of management costs were reported for reactive, post-invasion actions (84% of management costs, focused on eradication and control). Second, differences between costs in PAs and non-PAs varied among continents and environments. We found significantly higher IAS costs in terrestrial PA environments compared to non-PAs, while regionally, Europe incurred higher costs in PAs and Africa and Temperate Asia incurred higher costs in non-PAs. Third, characterization of drivers of IAS costs within PAs showed an effect of environments (higher costs in terrestrial environments), continents (higher in Africa and South America), taxa (higher in invertebrates and vertebrates than plants) and Human Development Index (higher in more developed countries). Globally, our findings indicate that, counterintuitively, PAs are subject to very high costs from biological invasions. This highlights the need for more resources to be invested in the management of IAS to achieve the role of PAs in ensuring the long term conservation of nature. Accordingly, more spatially-balanced and integrative studies involving both scientists and stakeholders are required.

Genome size variation in Cactaceae and its relationship with invasiveness and seed traits - Sara Lopes; Lucie Mota; Mariana Castro; Gabrielle Nobre; Ana Novoa; David M. Richardson; João Loureiro; Sílvia Castro (Biological Invasions, 2021)

Population structure of the European conger Conger conger from the mid‐North Atlantic Ocean inferred from bathymetric distribution, length composition and movement patterns analyses - Wendell Medeiros‐Leal; Régis Santos; Ana Novoa‐Pabon; Hélder Silva; Mario Pinho (Fisheries Management and Ecology, 2021)
Information about the population structure of Conger conger (L.) is scarce, being a limiting factor for fisheries assessment. To make available important baseline information and to test the hypothesis that the population in the mid‐North Atlantic (Azores region) represents a fishery management unit, fishery‐dependent and survey data relating to bathymetric distribution, length composition and movement patterns were examined. Fishing impacts were also evaluated using abundance and size trends over the last 25 years. The greatest abundance was in depths between 300 and 600 m. Sizes ranged from 14 to 260 cm, with larger individuals around seamounts. Tagging data showed a strong sedentary behaviour. Results combined with previous genetic and otolith studies indicated the stock in the Azores may represent a self‐contained population. Abundance and size trends were stable, but the species is considered vulnerable to overfishing due to its biological characteristics. Monitoring and adequate rational resource management are of utmost importance.

Invasion Culturomics and iEcology - Ivan Jarić; Céline Bellard; Ricardo A. Correia; Franck Courchamp; Karel Douda; Franz Essl; Jonathan M. Jeschke; Gregor Kalinkat; Lukáš Kalous; Robert J. Lennox; Ana Novoa; Raphaël Proulx; et al. (Conservation Biology, 2021)

A proposed unified framework to describe the management of biological invasions - Peter A. Robertson; Aileen Mill; Ana Novoa; Jonathan M. Jeschke; Franz Essl; Belinda Gallardo; Juergen Geist; Ivan Jarić; Xavier Lambin; Camille Musseau; Jan Pergl; Petr Pyšek; et al. (Biological Invasions, 2020)
Managing the impacts of invasive alien species (IAS) is a great societal challenge. A wide variety of terms have been used to describe the management of invasive alien species and the sequence in which they might be applied. This variety and lack of consistency creates uncertainty in the presentation and description of management in policy, science and practice. Here we expand on the existing description of the invasion process to develop an IAS management framework. We define the different forms of active management using a novel approach based on changes in species status, avoiding the need for stand-alone descriptions of management types, and provide a complete set of potential management activities. We propose a standardised set of management terminology as an emergent feature of this framework. We identified eight key forms of management: (1) pathway management, (2) interception, (3) limits to keeping, (4) secure keeping, (5) eradication, (6) complete reproductive removal, (7) containment and (8) suppression. We recognise four associated terms: prevention; captive management; rapid eradication; and long-term management, and note the use of impact mitigation and restoration as associated forms of management. We discuss the wider use of this framework and the supporting activities required to ensure management is well-targeted, cost-effective and makes best use of limited resources.

A conceptual map of invasion biology: Integrating hypotheses into a consensus network - Martin Enders; Frank Havemann; Florian Ruland; Maud Bernard‐Verdier; Jane A. Catford; Lorena Gómez‐Aparicio; Sylvia Haider; Tina Heger; Christoph Kueffer; Ingolf Kühn; Laura A. Meyerson; Camille Musseau; et al. (Global Ecology and Biogeography, 2020)
Background and aims Since its emergence in the mid‐20th century, invasion biology has matured into a productive research field addressing questions of fundamental and applied importance. Not only has the number of empirical studies increased through time, but also has the number of competing, overlapping and, in some cases, contradictory hypotheses about biological invasions. To make these contradictions and redundancies explicit, and to gain insight into the field’s current theoretical structure, we developed and applied a Delphi approach to create a consensus network of 39 existing invasion hypotheses. Results The resulting network was analysed with a link‐clustering algorithm that revealed five concept clusters (resource availability, biotic interaction, propagule, trait and Darwin’s clusters) representing complementary areas in the theory of invasion biology. The network also displays hypotheses that link two or more clusters, called connecting hypotheses , which are important in determining network structure. The network indicates hypotheses that are logically linked either positively (77 connections of support) or negatively (that is, they contradict each other; 6 connections). Significance The network visually synthesizes how invasion biology’s predominant hypotheses are conceptually related to each other, and thus, reveals an emergent structure – a conceptual map – that can serve as a navigation tool for scholars, practitioners and students, both inside and outside of the field of invasion biology, and guide the development of a more coherent foundation of theory. Additionally, the outlined approach can be more widely applied to create a conceptual map for the larger fields of ecology and biogeography.

Invasion syndromes: a systematic approach for predicting biological invasions and facilitating effective management - Ana Novoa; David M. Richardson; Petr Pyšek; Laura A. Meyerson; Sven Bacher; Susan Canavan; Jane A. Catford; Jan Čuda; Franz Essl; Llewellyn C. Foxcroft; Piero Genovesi; Heidi Hirsch; et al. (Biological Invasions, 2020)
Our ability to predict invasions has been hindered by the seemingly idiosyncratic context-dependency of individual invasions. However, we argue that robust and useful generalisations in invasion science can be made by considering “invasion syndromes” which we define as “a combination of pathways, alien species traits, and characteristics of the recipient ecosystem which collectively result in predictable dynamics and impacts, and that can be managed effectively using specific policy and management actions”. We describe this approach and outline examples that highlight its utility, including: cacti with clonal fragmentation in arid ecosystems; small aquatic organisms introduced through ballast water in harbours; large ranid frogs with frequent secondary transfers; piscivorous freshwater fishes in connected aquatic ecosystems; plant invasions in high-elevation areas; tall-statured grasses; and tree-feeding insects in forests with suitable hosts. We propose a systematic method for identifying and delimiting invasion syndromes. We argue that invasion syndromes can account for the context-dependency of biological invasions while incorporating insights from comparative studies. Adopting this approach will help to structure thinking, identify transferrable risk assessment and management lessons, and highlight similarities among events that were previously considered disparate invasion phenomena.

Elasmobranch species richness, fisheries, abundance and size composition in the Azores archipelago (NE Atlantic) - Régis Santos; Ana Novoa-Pabon; Hélder Silva; Mário Pinho (Marine Biology Research, 2020)

No evidence for novel weapons: biochemical recognition modulates early ontogenetic processes in native species and invasive acacias - Florencia A. Yannelli; Ana Novoa; Paula Lorenzo; Jonatan Rodríguez; Johannes J. Le Roux (Biological Invasions, 2020)

Cointroductions of Australian acacias and their rhizobial mutualists in the Southern Hemisphere - Staci Warrington; Allan Ellis; Ana Novoa; Elizabeth M. Wandrag; Philip E. Hulme; Richard P. Duncan; Alex Valentine; Johannes J. Le Roux (Journal of Biogeography, 2019)
Aim Mutualisms are often disrupted for plants introduced to new ranges, yet many of these plants have managed to obtain effective mutualistic associations in their new ranges. There are two potential pathways for non‐native plants to reassemble mutualisms: cointroduction (i.e. familiar associations with cointroduced mutualists) or ecological fitting (i.e. forming or adapting novel associations with resident native mutualists). We assessed the importance of each pathway for mutualist reassembly in four Australian Acacia species ( A. baileyana , A. dealbata , A. decurrens and A. melanoxylon ) and their associated nitrogen‐fixing rhizobial symbionts in two non‐native locations. Location Native ranges of acacias in south‐eastern Australia and two non‐native ranges in New Zealand and South Africa. Methods Rhizobia associated with each acacia species in each country were isolated and identified based on DNA sequencing of the housekeeping recA gene and the symbiotic nodA gene. Separate phylogenies were reconstructed for each gene region to infer biogeographic histories of acacia‐associated rhizobia. Selected rhizobial strains for each acacia species by country combination were used as inocula in a glasshouse experiment and early growth kinetics and nitrogen fixation efficiency of acacia seedlings were compared between inoculum treatments to determine symbiotic effectiveness. Results All isolated rhizobial strains belonged to the genus Bradyrhizobium . Phylogenetic analyses revealed almost no country‐ or species‐specific clusters of these strains for either gene region and indicated that most acacia‐associated bradyrhizobia in New Zealand and South Africa were cointroduced from Australia. These results were supported by little variation in the growth performances of acacia seedlings, irrespective of inoculum treatment. Main conclusions This study revealed that cointroduction of Australian acacias and their rhizobia may be more prevalent than previously thought. Additionally, a single rhizobium cointroduction event may be sufficient to facilitate the establishment of effective mutualisms in numerous Acacia species, potentially leading to an invasion meltdown.

Can we consider the stocks of alfonsinos Beryx splendens and Beryx decadactylus from the Azores a discrete fishery management unit? - Régis V. S. Santos; Ana M. Novoa‐Pabon; Hélder M. Silva; Mário R. Pinho (Journal of Fish Biology, 2019)
This paper summarises the detailed information on catch, fork length, weight, sex and maturity of alfonsinos Beryx splendens and Beryx decadactylus collected from targeted surveys in Azores waters, complemented by fishery data, over the past c . 20 years. To date, it was not possible to define if the Azorean component of the population can be considered as a discrete local management unit. The reason for this is the lack of available information for these resources covering the entire spatial distribution of the species in the North Atlantic Ocean. Additionally, there are some conflicts between the different genetic results available, poor understanding about the species movements and data from the Azores show some discrepancies in aspects of reproduction. Consequently, there is no analytical assessment for this resource and the stock of Beryx spp. is currently managed based on the precautionary approach. Outputs of recent analyses are presented in this study and possible assumptions and strategies for the assessment are discussed.

Stock structure of the common mora in the mid-North Atlantic (Azores archipelago) - Régis Santos; Ana Novoa-Pabon; Wendell Silva; Hélder Silva; Mário Pinho (Frontiers in Marine Science, 2019)

Demersal fish assemblages on seamounts potentially explored by fishing in the northeastern Atlantic - Régis Santos; Wendell Silva; Ana Novoa-Pabon; Hélder Silva; Mário Pinho (Frontiers in Marine Science, 2019)

Stock structure of the blackbelly rosefish in the mid-North Atlantic (Azores archipelago) - Régis Santos; Ana Novoa-Pabon; Wendell Silva; Hélder Silva; Mário Pinho (Frontiers in Marine Science, 2019)

Managing invasive species in cities: a decision support framework applied to Cape Town - Mirijam Gaertner; Ana Novoa; Jana Fried; David M. Richardson (Biological Invasions, 2017)

Does public awareness increase support for invasive species management? Promising evidence across taxa and landscape types - Ana Novoa; Katharina Dehnen-Schmutz; Jana Fried; Giovanni Vimercati (Biological Invasions, 2017)

Understanding the influence of urbanization on invasibility: Carpobrotus edulis as an exemplar - Yaiza Lechuga-Lago; Ana Novoa; Johannes J. Le Roux; Luís González (Biological Invasions, 2017)

Level of environmental threat posed by horticultural trade in Cactaceae - Ana Novoa; Johannes J. Le Roux; David M. Richardson; John R.U. Wilson (Conservation Biology, 2017)
Ornamental horticulture has been identified as an important threat to plant biodiversity and is a major pathway for plant invasions worldwide. In this context, the family Cactaceae is particularly challenging because it is considered the fifth most threatened large taxonomic group in the world; several species are among the most widespread and damaging invasive species; and Cactaceae is one of the most popular horticultural plant groups. Based on the Convention on International Trade in Endangered Species of Wild Flora and Fauna and the 11 largest online auction sites selling cacti, we documented the international cactus trade. To provide an in‐depth look at the dynamics of the industry, we surveyed the businesses involved in the cactus trade in South Africa (a hotspot of cactus trade and invasions). We purchased seeds of every available species and used DNA barcoding to identify species to the genus level. Although

Resolving a Prickly Situation: Involving Stakeholders in Invasive Cactus Management in South Africa - Ana Novoa; Haylee Kaplan; John R. U. Wilson; David M. Richardson (Environmental Management, 2016)

GATG Dendrimers and PEGylated Block Copolymers: from Synthesis to Bioapplications - Ana Sousa-Herves; Ramon Novoa-Carballal; Ricardo Riguera; Eduardo Fernandez-Megia (The AAPS Journal, 2014)